Tricarboxylate-based GdIII coordination polymers exhibiting large magnetocaloric effects. Issue 22 (12th May 2016) - Liu, Sui-Jun; Cao, Chen; Xie, Chen-Chao; Zheng, Teng-Fei; Tong, Xiao-Lan; Liao, Jin-Sheng; Chen, Jing-Lin; Wen, He-Rui; Chang, Ze; Bu, Xian-He
Abstract : Hydrothermal reactions of Gd2 O3 and two tricarboxylates generated two carboxylate-bridged 2D/3D Gd III coordination polymers with large magnetocaloric effects. Abstract : Two Gd III coordination polymers with the formula [Gd(cit)(H2 O)]∞ (1 ) and [Gd(nta)(H2 O)2 ]∞ (2 ) (H4 cit = citric acid, H3 nta = nitrilotriacetic acid) have been successfully prepared under hydrothermal conditions. Complex1 exhibits a three-dimensional (3D) structure based on carboxylate-bridged layers, while complex2 is a double-layer structure containing eight-coordinated Gd III . Magnetic investigations reveal that weak antiferromagnetic couplings between adjacent Gd III ions in both1 and2 with different Weiss values result in large cryogenic magnetocaloric effects. It is notable that the maximum entropy changes (−Δ S maxm) of1 and2 reach 31.3 J kg −1 K −1 and 32.2 J kg −1 K −1 at 2 K for a moderate field change (Δ H = 3 T), and a remarkable −Δ S maxm (41.5 J kg −1 K −1 for1 and 42.0 J kg −1 K −1 for2 ) could be obtained for Δ H = 7 T.